Interaction between Bacillus anthracis and Pattern-Recognizing Receptors of Innate and Adaptive Immunity - P. Yu. Popova; N. I. Mikshis; T. N. Shchukovskaya; Yu. A. Popov (Проблемы особо опасных инфекций, 2011)
According to modern views, protection of an organism from different pathogens is achieved through functioning of the two chains of immune system - innate and acquired ones. Initially, receptors of non-specific immunity, including Toll-like receptors, identify conservative pathogen-associated molecular structures. The subsequent activation of signaling pathways leads to rapid neutralization and elimination of foreign agent. Concurrently, initiation of the adaptive immunity, and realization of pro-inflammatory reactions' cascade take place. The review summarizes literature data concerning peculiarities of innate and adaptive types of immunity in case of interaction between macro-organism and Bacillus anthracis. Protective antigen, lipoprotein, cell wall components, anthrolysine O, CpG DNA sequence and others are the potential ligands of Toll-like receptors in B. anthracis. Demonstrated are the results of experiments that bear evidence of the fact, that synthetic agonists of Toll-like receptors influence realization of B. anthracis cytotoxicity and course of infection in laboratory animals. Modificators of Toll-like receptor functions can be used as immunostimulators for designing of effective means of anti-infectious protection. Innate and adaptive components of the immunity, having their own unique mechanisms of the specific B. anthracis identification, interact with each other, strengthen and complement each other.